2009
DOI: 10.5144/0256-4947.2009.212
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of allergic fungal sinusitis among patients with nasal polyps

Abstract: BACKGROUND:Nasal polyposis is a common problem in the eastern province of Saudi Arabia. Since allergic fungal sinusitis (AFS) can present with unilateral or bilateral nasal polyps, it is important to be aware of the prevalence of AFS in patients with nasal polyps.PATIENTS AND METHODS:The medical records of 91 patients with nasal polyps admitted for functional endoscopic sinus surgery were reviewed. The diagnosis of AFS was considered if histopathology showed the presence of eosinophillic mucin-containing hypha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 10 publications
1
24
1
Order By: Relevance
“…Telmesani reported 12.1% (11/91) incidence of allergic fungal sinusitis among patients with nasal polyps. [4] CT scan of the patient showed multiple sinus involvement with marked opacity in left and right maxillary sinus. In study by Alrajhi et al, abnormalities of paranasal sinuses were noted on CT scan in all patients; all sinuses were involved in 61% of patients.…”
Section: Discussionmentioning
confidence: 96%
“…Telmesani reported 12.1% (11/91) incidence of allergic fungal sinusitis among patients with nasal polyps. [4] CT scan of the patient showed multiple sinus involvement with marked opacity in left and right maxillary sinus. In study by Alrajhi et al, abnormalities of paranasal sinuses were noted on CT scan in all patients; all sinuses were involved in 61% of patients.…”
Section: Discussionmentioning
confidence: 96%
“…Other study reported 6.7% prevalence of fungal sinusitis in Brazil (7) . The prevalence of allergic fungal sinusitis is about 12.1% among patients in Saudi Arabia (8) . .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the presence of radiologic bony expansion or erosion, eosinophilic mucus without fungal invasion, and positive fungal cultures were identified in the majority of AFRS patients. AFRS can be caused by a variety of organisms, the most common of which include Aspergillus and Curvularia spp [14], and it remains a relatively common disease (10% to 30% of patients with nasal polyps also have AFRS) [15,16]. Yet, despite its prevalence, AFRS has often been difficult to diagnose accurately because on physical examination it is similar to chronic rhinosinusitis.…”
Section: Allergic Fungal Rhinosinusitismentioning
confidence: 98%